Intracellular delivery of therapeutic proteins. New advancements and future directions - Porello, Ilaria; Cellesi, Francesco (Frontiers in Bioengineering and Biotechnology, 2023)
Achieving the full potential of therapeutic proteins to access and target intracellular receptors will have enormous benefits in advancing human health and fighting disease. Existing strategies for intracellular protein delivery, such as chemical modification and nanocarrier-based protein delivery approaches, have shown promise but with limited efficiency and safety concerns. The development of more effective and versatile delivery tools is crucial for the safe and effective use of protein drugs. Nanosystems that can trigger endocytosis and endosomal disruption, or directly deliver proteins into the cytosol, are essential for successful therapeutic effects. This article aims to provide a brief overview of the current methods for intracellular protein delivery to mammalian cells, highlighting current challenges, new developments, and future research opportunities.